Comprehensive Analysis of the Effect of Ultrasonic Surface Rolling Process on the Friction and Wear Properties of TB8 Titanium Alloy - Liu, Yu; Cui, Hao; Liu, Ying; Zhao, Xiaohui (Journal of materials engineering and performance, 2023)
The bio-tribological properties of TB8 titanium alloy treated by ultrasonic surface rolling were studied in the present work. Friction and wear tests were carried out in 15% hyaluronic acid solution. Surface characteristics including morphology, chemical composition, and mechanical properties were investigated to discuss the influence of the ultrasonic surface rolling process on material transfer, tribofilms, and wear mechanisms. Experimental results showed that the highest tensile strength, hardness, and the smallest surface roughness were obtained under 600 N ultrasonic surface rolling process (the highest load within the selected parameter range). The best friction and wear properties correspondingly occurred in 600 N ultrasonic surface rolled samples. The smoothest and densest oxide layers composed of TiO 2 , TiC, and TiC x O y were found on the friction interfaces of these samples to protect TB8 substrate from further oxidation. Meanwhile, the observed strong relevance between mechanical properties and specific wear rate as well as friction coefficient also revealed that the intrinsic plastic gradient of ultrasonic surface rolled layer can significantly improve the friction and wear properties of TB8 titanium alloy.